How emerging Europe came through the 2008/09 crisis : an account by the staff of the IMF's European Department - Bakker, Bas Berend; Klingen, Christoph; International Monetary Fund. European Department (Washington, D.C. International Monetary Fund, 2012)
Emerging Europe was particularly hard hit by the global financial crisis, but a concerted effort by local policymakers and the international community staved off impending financial meltdown and laid the foundations for renewed convergence with western Europe. This book, written by staff of the IMF's European Department that worked on the region at the time, provides a unique account of events: the origins of the crisis and the precrisis policy setting; the crisis trigger and the scramble to avoid the worst; the stabilization and recovery; the remaining challenges; and the lessons for the future.
Includes bibliographical references and index.
Also available online.
oif 29/07/15
Loan
Keywords: Global Financial Crisis, 2008-2009.; Financial crises -- Europe; Financial crises -- Developing countries; International Monetary Fund -- Europe; International Monetary Fund -- Developing countries